UPPER STRUCTURE DESIGN AND SEISMIC PERFORMANCE EVALUATION OF L-SHAPE OFFICE BUILDINGS IN BANDUNG USING DILATED AND NON-DILATED SYSTEMS - Qonitalillah
This final project describes the process of designing and checking the seismic performance of a structure in two different conditions, namely with dilation and without dilation. The structure under review is a structure with L-shaped asymmetric geometry in Bandung which functioned as an office building with 13 floors and 2 basements. The structure is designed based on SNI 2847:2019 with earthquake loading analysis using spectral response analysis referring to SNI 1726: 2019. The results obtained that the selection of the appropriate position of the shear wall on the non-dilated structure can reduce the torsion irregularities. Meanwhile, the presence of structural separators in the dilated structure can effectively reduce irregularities in the structure and produce a more efficient design. The design results were further evaluated using pushover analysis and obtained that both structural systems are at the level of Immediate Occupancy performance in the X and Y directions based on the classification according to the magnitude of drift in the ATC-40 standard. It is also shown that structures with dilated systems have superior ductility and lower damage levels when compared to non-dilated structures. Meanwhile, non-dilated structures have better performance and capacity to withstand lateral deformation, ability to withstand earthquake loads, and have better structural safety and stability on both orthogonal axes. The evaluation results obtained can be different for structures with variations in configuration and geometry of elements and different structural systems.